2001
DOI: 10.1159/000050938
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Inguinal Hernias Using the Mesh Technique during Extraperitoneal Pelvic Lymph Node Dissection

Abstract: Purpose: This article describes our experience of using a totally extraperitoneal approach for endoscopic pelvic lymphadenectomy and inguinal hernia repair with the mesh technique in one procedure. Materials and Methods: A total of 52 patients underwent modified pelvic lymph node dissection for the staging of prostate cancer. Eight of them had hernia defects; 1 was recurrent. Five patients with direct and 3 patients with indirect inguinal hernias were treated by totally extraperitoneal hernia repair with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Especially in elderly men, the incidence of inguinal hernia is relatively high. Different authors reported a concomitant inguinal hernia repair during endoscopic extraperitoneal pelvic lymph node dissection [35,36]. In these studies, the rate of inguinal hernias was 12.9-18.3%.…”
Section: Endoscopic Prostatectomy and Concomitant Hernia Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in elderly men, the incidence of inguinal hernia is relatively high. Different authors reported a concomitant inguinal hernia repair during endoscopic extraperitoneal pelvic lymph node dissection [35,36]. In these studies, the rate of inguinal hernias was 12.9-18.3%.…”
Section: Endoscopic Prostatectomy and Concomitant Hernia Repairmentioning
confidence: 99%
“…We prefer a standardized TEP technique, which uses the principle of tension-less hernia repair, overlaying the entire myopectineal orifice with one large piece of mesh [36,37]. The mesh is 10 ¥ 15 cm; it is incised in the middle and a small hole cut into the mesh to provide sufficient space for the spermatic cord.…”
Section: Endoscopic Prostatectomy and Concomitant Hernia Repairmentioning
confidence: 99%
“…7,9,10 Furthermore, the extraperitoneal endoscopic hernia repair can be safely performed with endoscopic extraperitoneal lymph node dissection during one procedure. 11,12 28 STOLZENBURG ET AL.…”
Section: Introduction L Aparoscopic Radical Prostatectomy (Lrp) Is Amentioning
confidence: 99%